Management of Respiratory Failure in Patients with COVID-19 and Multiple Myeloma - Slamet Hadi Santoso; Arie Zainul Fatoni (Journal of Anaesthesia and Pain, 2022)
Background: Cancer patients have higher risk of getting COVID-19. Individuals with malignancy who infected COVID-19 often underwent prolonged hospitalization or death. Here, we report respiratory failure management of of COVID-19 patient with multiple myeloma (MM).Case: A 66-year-old man came with complaints of shortness of breath. The patient was intubated and treated in the intensive care COVID. Patients with a history of multiple myeloma and who have chemotherapy cycle. The laboratory results showed an increase in markers of inflammation, hypoalbuminemia, and bicytopenia. The results of the polymerase chain reaction swab were positive.  There are 4 managements in this patient, airway management: intubation and ventilator settings using the Lung Protective Strategy principle. Management Breathing: administration of antibiotics according to sputum culture results. Circulation Management: Fluid management using a non-invasive Contractility Index (ICON) monitor. Management of Disability: Spontaneous Awakening Trial (SAT) and Spontaneous Breathing Trial (SBT) when the aggravating disease has been handled.Conclusion: Management of respiratory failure in patients with multiple myeloma and COVID-19 infection is primarily focused on supportive care such as airway management, breathing management, fluid management and disability management.